Characterization of hybridization within a secondary contact region of the inshore fish, Bostrychus sinensis, in the East China Sea. (January 2018) - Ding, Shaoxiong; Mishra, Mrinal; Wu, Haohao; Liang, Shuang; Miyamoto, Michael
Abstract The northwest Pacific marginal seas are a primary center of phylogeographic and evolutionary research, because of their dynamic geographic history of falling and rising sea levels during the glaciations and interglaciations of the last one million years. Here we present new molecular and morphological data for geographic samples of the four-eyed sleeper (Bostrychus sinensis ), which reinforce the evidence for secondary contact and hybridization between two phylogeographic lineages in the East China Sea. Specifically, we find that the secondary contact region is characterized by a low frequency of hybridization, where mitochondrial DNA introgression is relatively common, whereas F1 hybrids are correspondingly scarce. Furthermore, the adult standard lengths of the two phylogeographic lineages vary geographically in a manner that is consistent with reproductive character displacement. Collectively, the molecular and morphological data document that sleeper hybridization conforms to the classic "tension zone" model, where alleles are lost via reduced hybrid viability and/or positive assortative mating but are then replenished by dispersal from south of the secondary contact region. They also indicate that the two phylogeographic lineages are at an incipient stage of the speciation process. These results and conclusions for the four-eyed sleeper are presented as a case study for future research on the vicariance, secondary contact, and hybridization of marine groups in the northwest Pacific marginal seas.